Seasonal Occurence of Food and Feeding Habit of Labeo bata(Hamilton) (Cypriniformes : Cyprinidae) (Journal of Science Foundation, 2015)
Food and feeding habits of fishes have a great significance in aquaculture practices. It helps to select such species of fishes for culture which will utilize all the available potential food of the water bodies without much competition with one another but will live in association with other fishes. This paper deals with the feeding intensity and food habits of L. bata . Food and feeding habit of freshwater minor carp Labeo bata (120 to 250 mm total length) were studied. The fish is a herbivore, feeding mainly on algae (22.32 %), higher plant parts (31.26 %), protozoans (7.42 %), crustaceans (15.33 %), insects (3.56 %), muds, sand, debris and detritus (16.32 %) and unidentified food materials (3.99%).Journal of Science Foundation, 2014;12(1):7-15